2006
DOI: 10.1007/s10517-006-0277-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in nitric oxide content in healthy and hypertensive rats at rest and under stress conditions

Abstract: Immobilization was followed by an increase in blood NO concentration in male and female rats. After renovascular hypertension modeling blood pressure was higher and the decrease in nitric oxide concentration was more pronounced in males than in females. The levels of nitric oxide in healthy and hypertensive females at rest and during stress were higher than in males. These specific features probably contribute to higher resistance of the cardiovascular system in females to pathological changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 11 publications
7
19
0
Order By: Relevance
“…Experimental and epidemiological studies have reported blunted NO production in males relative to females (13,16,29). The results of this study provide mechanistic support for the hypothesis that renal NO levels are lower in male SHR compared with females.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Experimental and epidemiological studies have reported blunted NO production in males relative to females (13,16,29). The results of this study provide mechanistic support for the hypothesis that renal NO levels are lower in male SHR compared with females.…”
Section: Discussionsupporting
confidence: 78%
“…Whole body NO levels have been reported to be greater in females compared with males (13,16,29,36), and a sex difference in the NO pathway may contribute to sexual dimorphisms in cardiovascular and renal pathologies. Under normotensive conditions female rats have been shown to have greater renal NOS1 immunoreactivity and NOS3 protein expression (22,36,40,55).…”
mentioning
confidence: 99%
“…These data are consistent with the results of our previous studies showing that the development of hypertension is accompanied by reduction of NO generation [1]. Indomethacin injection was followed by the pressor infl uences, whose amplitude did not differ in animals of two experimental groups (17-22 and 19-23%, respectively; p<0.05).…”
Section: Resultssupporting
confidence: 92%
“…Therefore, androgens have a stimulatory effect on functional activity of K ATP channels, which is reduced during hypertension. The stimulatory effects of testosterone on K ATP channels were observed in in vitro experiments on large vessels (e.g., aorta) [1] and in in vivo studies on coronary arteries [6].…”
Section: Resultsmentioning
confidence: 92%
“…In addition, females are characterized by cyclic changes in ovarian function associated with the development of follicles, ovulation, and corpora lutea formation. Variations of the hormonal profile during different phases of the estrous cycle modulate the course of stress reaction and processes in the hemostasis system [4].…”
mentioning
confidence: 99%